Epidemiological and clinical features of human rabies cases in Bali 2008-2010 - Susilawathi, Ni M (BioMed Central, 2012)
BACKGROUND: Previously thought to be rabies free, Bali experienced an outbreak of animal and human rabies cases in November 2008. We describe the epidemiological and clinical data of human rabies cases occurring in the first two years of the outbreak. METHODS: We analysed the patient records of all rabies cases from the Sanglah General Hospital in Denpasar, and district hospitals in Buleleng and Tabanan. A conventional reverse transcriptase polymerase chain reaction was developed to detect the rabies virus genome in saliva, corneal swabs, and ante- and post-mortem cerebrospinal fluid (CSF). RESULTS: There were 104 human rabies cases in Bali during November 2008-November 2010. Patients' mean age was 36.6 years (range 3-84 years; SD 20.7), most were male (56.7%), and originated from rural districts. Almost all (92%) cases had a history of dog bite. Only 5.8% had their wounds treated and received an anti-rabies vaccine (ARV) after the bite incident. No patients received rabies immunoglobulin (RIG). The estimated time from dog bite to the onset of signs and symptoms was 110.4 days (range 12-720 days; SD 118.2). The mean length of medical care until death was 21.8 hours (range 1-220 hours; SD 32.6). Less than 50% of patients had prodromal symptoms. The most frequent prodromal symptom was pain or paraesthesia at the bite site (37.6%). The two most common central nervous system infection signs were agitation (89.2%) and confusion (83.3%). Signs of autonomic nervous system dysfunction included hydrophobia (93.1%), hypersalivation (88.2%), and dyspnea (74.4%). On admission, 22 of 102 patients (21.6%) showed paralytic manifestations, while the rest (78.4%) showed furious rabies manifestations. The case-fatality rate was 100%. The rabies virus genome was detected in 50 of 101 patients (49.5%) with the highest detection rate from post-mortem CSF samples. CONCLUSIONS: Rabies is a major public health problem in Bali. Human fatalities occur because of a lack of knowledge regarding rabies risk, the poor management of dog bites, and the limited availability of RIG. Increasing public awareness of dog bite management, increasing the availability of ARV and RIG, and implementing an island-wide dog vaccination campaign will help prevent human rabies cases.